Effective Professional Development for Teachers to Foster Students' Academic Language Proficiency Across the Curriculum: A Systematic Review - Eva Kalinowski; Anna Gronostaj; Miriam Vock (SAGE Publishing, 2019)
This review summarizes features of professional development programs that aim to prepare in-service teachers to improve students' academic language proficiency when teaching subject areas. The 38 studies reviewed suggest that all of the profiled interventions were effective to some extent. The programs share many characteristics considered important in successful teacher professional development across different subject areas. They also include some features that appear to be specific to teacher training in this particular domain. This review supports the idea that professional development helps change teachers' thinking and practice and benefits students, if certain features are taken into consideration in its design and implementation.